Catfish Oil (Pangasius hypophthalmus) effect to ferritin and sTfR in iron deficiency anemia - Hersanti Sulistyaningrum; Fronthea Swastawati; Maria Mexitalia; Etika Ratna Noer (Jurnal Gizi Indonesia (The Indonesian Journal of Nutrition), 2021)
Background: Iron deficiency anemia is a micronutrient problem and the prevalence is still high. Catfish oil (Pangasius hypophthalmus) is a natural source of heme iron which can improve body iron levels.Objectives: This study was aimed to examine and analyze the effect of catfish oil on ferritin and sTfR levels in male wistar rats with iron deficiency anemia models.Materials and Methods: This study was conducted on male wistar rats which were divided into groups C- (standard feed), C+ (standard feed but had the iron removed), X1 (standard feed without iron but was supplemented with catfish oil), X2 (standard feed without iron but was supplemented with ferrous sulfate) for 14 days. Ferritin and sTfR levels were measured before and after intervention using ELISA.Results: The study showed an increase ferritin levels in X1 (21.87 ng/ml ±0.76), X2 (24.47 ng/ml ±0.54) and there was no significant difference between the two (p=0.069; p>0.05); a decrease in C- (0.25 ng/ml ±0.43), C+ (0.32 ng/ml ±0.059) (p=0.00; p<0.05). The sTfR levels decreased before and after intervention (p=0.00; p<0.05) in C+ (0.24 μ/mL ±0.99), X1 (60.66 μ/mL ±0.29), X2 (62.10 μ/mL ±0.90) and increased in C- (0.40 μ/mL ±0.97).Conclusions: The study indicates ferritin levels increased in the rats receiving catfish oil is not different from the rats that received ferrous sulfate and sTfR levels decreased significantly in wistar rats with iron deficiency anemia receiving catfish oil although the results were not as good as ferrous sulfate supplementation